Sustaining Water Systems in Rural and Small Towns in Ghana: The Role of Traditional Authorities in the Krachi West District - Boasinke, Raymond Kwasi; Braimah, Imoro (European Scientific Journal, ESJ, 2022)
The sustainability of water systems in rural communities and small towns in Ghana has been a major challenge that has engaged the attention of government, Non-governmental Organisations, and academics. There have been several attempts at developing models that will ensure the sustainability of water systems in Ghana. This study examined the role of traditional authorities in the management of water systems in rural communities and small towns in the Krachi West District in the Oti Region of Ghana. Using a qualitative research design, the study purposely selected and interviewed 69 respondents. The study revealed that traditional authorities play critical roles in ensuring the sustainable management of water systems in rural communities and small towns in Ghana. It also revealed that respondents want a community management model that has traditional authorities as members of an official advisory board to the Water and Sanitation Management Teams (WSMTs). It further revealed that the traditional authorities and the WSMTs have a cordial working relationship. The study, therefore, recommends that traditional authorities should officially be recognised and their roles spelled out in the community management model of water systems in Ghana.